2003
DOI: 10.1023/b:hijo.0000020883.33256.fe
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Effects of Dexamethasone on the Gene Expression of Cbfa1, Osterix and Bone Matrix Proteins During Differentiation of Cultured Primary Rat Osteoblasts

Abstract: Runx2/core binding factor alpha 1 (Cbfa1) and Osterix (Osx) are osteoblast-specific transcription factors essential for the development of a mature osteoblast phenotype and are thought to activate osteoblast marker genes in vivo to produce a bone-specific matrix. Dexamethasone (Dex) is known to be a potent stimulator of osteoblastic differentiation in vitro, however, the exact role is still unclear. To investigate the mechanisms of the stimulation of osteoblastic differentiation by Dex, we evaluated the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 39 publications
4
64
0
5
Order By: Relevance
“…On the other hand, dexamethasone-treated osteoblasts underwent a concurrent down-regulation of E4BP4 and increased expression of both Runx2 and Osterix. Although E4BP4 is induced by dexamethasone in osteoblasts (21), this up-regulation in response to dexamethasone is in line with other studies (42), and correlates with its concomitant inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, dexamethasone-treated osteoblasts underwent a concurrent down-regulation of E4BP4 and increased expression of both Runx2 and Osterix. Although E4BP4 is induced by dexamethasone in osteoblasts (21), this up-regulation in response to dexamethasone is in line with other studies (42), and correlates with its concomitant inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…However, overexpression of Osx in ES cells was unexpectedly found to upregulate Runx2/Cbfa1 expression [15] as a result of a possible feedback mechanism of Osx to Cbfa1. However, the overexpression of Osx in the latter study was performed in the presence of dexamethasone, which is a potent stimulator of osteogenic commitment and differentiation in vitro [26,27], and increases the expression of Runx2/Cbfa1 and Osx in differentiating fetal rat calvarial cells [28]. In our studies, osteogenic media that included 10 −8 M dexamethasone also increased levels of Cbfa1 and Osx in murine BMSC.…”
Section: Expression Pattern Of Osx and Runx2/cbfa1 In Bmsc Transducedmentioning
confidence: 58%
“…However, our study shows for the first time that overexpression of Osx in adult BMSC leads to the increased expression of osteogenic differentiation markers (OC, AP, BSP, and OPN) under experimental conditions that do not affect Runx2/Cbfa1 expression. The finding that RCAS-Osx transduced BMSC did not exhibit an upregulated expression of Runx2/Cbfa1 was not surprising, based on a previous report However, the overexpression of Osx in the latter study was performed in the presence of dexamethasone, which is a potent stimulator of osteogenic commitment and differentiation in vitro [26,27], and increases the expression of Runx2/Cbfa1 and Osx in differentiating fetal rat calvarial cells [28]. In our studies, osteogenic media that included 10 −8 M dexamethasone also increased levels of Cbfa1 and Osx in murine BMSC.…”
Section: Expression Pattern Of Osx and Runx2/cbfa1 In Bmsc Transducedmentioning
confidence: 62%
“…It has been reported that overexpression of BMP-2 inhibited the growth of a cell line derived from rat osteosarcoma, though it promoted their osteogenic differentiation (Huang et al, 2002). Other reports also indicated that proliferative abilities of osteoblasts and MSCs are influenced by osteogenic induction (Lee et al, 2004;Igarashi et al, 2004;Cho et al, 2005). It is generally believed that osteogenic induction on pluripotent cells with gene therapy approaches or chemical inducement decreases their proliferation rate.…”
Section: Discussionmentioning
confidence: 99%